Studi kasus : Enukleasi bulbi pada kucing dengan suspek chlamydia dengan metode trans-palpebral - Desty Apritya; Fradika Cahya Faresy; Michel Richard Sanjaya; Amelia Yolanda; Karolus Aurelius Sau; Devy Merry Angelia; Ni Made Dewi Lestari; Muhammad Wahyu Prabowo; Desty Apritya; Ratna Widyawati; Muhammad Noor Rahman (VITEK : Bidang Kedokteran Hewan, 2022)
A domestic cat, named London, 1 year old, and female. Condition with red swollen eyes and white and watery membranes. The cat's right eyeball is covered with a white layer. The eyelids are swollen, red, and sticking out, making it difficult for the cat to open her eyes. The eyes emit a greenish-yellow discharge. Based on the blood examination, she had anemia caused by vitamin B12 deficiency. The action taken to treat this case is bulbar enucleation surgery using the Trans-Palpebrae (Closed) technique. Postoperative systemic therapy was given by giving Cefotaxime injection and Tolfedin injection, while for oral therapy using a combination of drugs: Amoxicillin, Cyproheptadine, Caviplex